2021
DOI: 10.52403/ijrr.20211101
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Interleukin-6 Levels and Clinical Response to Anthracycline-Based Neoadjuvant Chemotherapy Regimen in Locally Advanced Breast Cancer Patients

Abstract: Background: Neoadjuvant chemotherapy is the initial therapy and the main pillar of treatment for locally advanced breast cancer (LABC). Currently, there is marker that widely accepted as a predictive factor for chemotherapy response in LABC. Elevated serum interleukin-6 (IL-6) levels and tumor sites have been proposed as prognostic markers for breast cancer. In this study, we aimed to examine the association between serum IL-6 levels with clinical response after the administration of neoadjuvant chemotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…In this study, a cut-off point of IL-6 serum levels in the non-MBC and MBC groups was obtained based on the previous study. Pratama et al (Pratama et al, 2021) suggested that the limit value for IL-6 serum levels to detect the possibility of metastases was >15.495 pg/mL. From the analysis of this study, it was found that there was a statistically significant relationship between IL-6 serum levels and the incidence of metastasis (P = 0.001).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…In this study, a cut-off point of IL-6 serum levels in the non-MBC and MBC groups was obtained based on the previous study. Pratama et al (Pratama et al, 2021) suggested that the limit value for IL-6 serum levels to detect the possibility of metastases was >15.495 pg/mL. From the analysis of this study, it was found that there was a statistically significant relationship between IL-6 serum levels and the incidence of metastasis (P = 0.001).…”
Section: Resultsmentioning
confidence: 52%
“…Previous research by Pratama (2021), showed that IL-6 levels above 15,495 pg/ml were associated with increased severity of breast cancer, characterized by a worsening of the cancer response to chemotherapy. (Pratama, 2021) At the moment, there are no biological factors from the tumor that can be used clinically as acceptable predictive factors of distant metastases in breast cancer. Therefore, in this study we aimed to measure serum IL-6 levels which play an important role in the pathogenesis of the metastatic process of non-MBC patients compared to MBC, to assess whether serum IL-6 levels can be alternative as a marker of tumor progression.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations